Indicators linking health and sustainability in the post-2015 development agenda. Issue 9965 (24th January 2015) - Dora, Carlos; Haines, Andy; Balbus, John; Fletcher, Elaine; Adair-Rohani, Heather; Alabaster, Graham; Hossain, Rifat; de Onis, Mercedes; Branca, Francesco; Neira, Maria
Summary: The UN-led discussion about the post-2015 sustainable development agenda provides an opportunity to develop indicators and targets that show the importance of health as a precondition for and an outcome of policies to promote sustainable development. Health as a precondition for development has received considerable attention in terms of achievement of health-related Millennium Development Goals (MDGs), addressing growing challenges of non-communicable diseases, and ensuring universal health coverage. Much less attention has been devoted to health as an outcome of sustainable development and to indicators that show both changes in exposure to health-related risks and progress towards environmental sustainability. We present a rationale and methods for the selection of health-related indicators to measure progress of post-2015 development goals in non-health sectors. The proposed indicators show the ancillary benefits to health and health equity (co-benefits) of sustainable development policies, particularly those to reduce greenhouse gas emissions and increase resilience to environmental change. We use illustrative examples from four thematic areas: cities, food and agriculture, energy, and water and sanitation. Embedding of a range of health-related indicators in the post-2015 goals can help to raise awareness of the probable health gains from sustainable development policies, thus making them more attractive to decision makers and more likely to be implemented than before.